Rad51 prevents Mre11-dependent degradation and excessive primpol-mediated elongation of nascent DNA after UV irradiation - Vallerga, María Belén (2015)
After UV irradiation, DNA polymerases specialized in translesion DNA synthesis (TLS) aid DNA replication. However, it is unclear whether other mechanisms also facilitate the elongation of UV-damaged DNA. We wondered if Rad51 recombinase (Rad51), a factor that escorts replication forks, aids replication across UV lesions. We found that depletion of Rad51 impairs S-phase progression and increases cell death after UV irradiation. Interestingly, Rad51 and the TLS polymerase polη modulate the elongation of nascent DNA in different ways, suggesting that DNA elongation after UV irradiation does not exclusively rely on TLS events. In particular, Rad51 protects the DNA synthesized immediately before UV irradiation from degradation and avoids excessive elongation of nascent DNA after UV irradiation. In Rad51-depleted samples, the degradation of DNA was limited to the first minutes after UV irradiation and required the exonuclease activity of the double strand break repair nuclease (Mre11). The persistent dysregulation of nascent DNA elongation after Rad51 knockdown required Mre11, but not its exonuclease activity, and PrimPol, a DNA polymerase with primase activity. By showing a crucial contribution of Rad51 to the synthesis of nascent DNA, our results reveal an unanticipated complexity in the regulation of DNA elongation across UV-damaged templates.